"Please don't buy!": Consumers attitude to alternative luxury consumption. (8th January 2021) - Guzzetti, Alice; Crespi, Roberta; Belvedere, Valeria
Abstract: Collaborative luxury consumption is driven both by product‐related and experience‐related motivations. The present study investigates the underlying factors that drive consumers to acquire and rent vintage and secondhand luxury products, applying a framework based on product‐related and experience‐related motivations. Findings reveal how vintage and secondhand are nurtured by anti‐consumption tendencies and recreational motives, while luxury renting is more driven by utilitarian reasons.